ANIME DISTRO: THE THEMATIC CLOTHING STORE IN YOGYAKARTA AND ITS INTERNET MARKETING - , SURYA ANDI NUGRAHA, Nur Endah Nugrahaeni, S.S., MA. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The aim of this graduating paper is to explain the profile of Anime Distro as one of clothing stores with Anime as its theme. Besides, this graduating paper describes the history of Anime Distro before it was established and it also describes its products. Then, it also describes of how Anime Distro can attract many customers by its marketing strategies, especially with internet marketing. The research methods used by the writer to gather the information and data of this graduating paper are direct observation and personal interview. The direct observation had done since February until May 2014 by the writer as the shopkeeper. Meanwhile, the personal interview with the owner and one of the employees of Anime Distro had done on May 14, 2014. Besides, in order to get the accurate data, the writer observed and visited the websites of Anime Distro. Based on direct observation and personal interview which were done by the writer, the writer can describe the profile of Anime Distro in detail. Moreover, the writer also was able to reveal the marketing strategies which were used by Anime Distro.